1969
DOI: 10.1002/art.1780120102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human rheumatoid factor on numbers of antibody‐producing cells

Abstract: whether the macroglobulins having antiIgG specificity (rheumatoid factors) that occur spontaneously during the course of human peripheral rheumatoid arthritis could similarly influence an immune response to human IgG. To date, no homeostatic function has been demonstrated for this group of macroglobulins, which occur with such regularity and in such high concentrations in the course of this disease. In the present investigation, human IgM rheumatoid factor is shown to decrease the number of mouse spleen cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1969
1969
1972
1972

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Patients with gout gave increased rosette counts. These authors suggested that the lymphocyte response of the rheumatoid individual precedes the appearance of humoral rheumatoid factors and that the process may correspond to that found in animals after immunization (Brown and Epstein, 1969).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Patients with gout gave increased rosette counts. These authors suggested that the lymphocyte response of the rheumatoid individual precedes the appearance of humoral rheumatoid factors and that the process may correspond to that found in animals after immunization (Brown and Epstein, 1969).…”
mentioning
confidence: 71%
“…Patients with gout gave increased rosette counts. These authors suggested that the lymphocyte response of the rheumatoid individual precedes the appearance of humoral rheumatoid factors and that the process may correspond to that found in animals after immunization (Brown and Epstein, 1969).In order to examine the properties and occurrence of rosette-forming lymphocytes, we have tested lymphocyte preparations from normal subjects of various ages, patients suffering from rheumatoid arthritis, and patients with orthopaedic conditions not related to rheumatoid arthritis. …”
mentioning
confidence: 99%